Thin steel plates exposed to combined ballistic impact and partially confined airblast loading. (February 2023) - Elveli, Benjamin Stavnar; Vestrum, Ole; Hauge, Knut Ove; Berstad, Torodd; Børvik, Tore; Aune, Vegard
Abstract: Pre-formed defects created by high-velocity impact have the potential to reduce the structural integrity of lightweight, flexible structures. This study evaluates the effect of complex, partially confined detonations on thin steel plates with realistic pre-formed defects. Target plates containing pre-cut circular holes with a diameter of 8.0 mm are compared to target plates exposed to an initial ballistic impact from 7.62 mm APM2 projectiles. The target plates were exposed to blast loading generated from detonating C-4 inside a steel tube. The stand-off distance was fixed and set equal to the tube radius, where the rear end of the tube was kept open. All blast tests were recorded with several pressure sensors, synchronized with two high-speed cameras monitoring the dynamic response of the target plates. This allowed for a reliable experimental procedure, serving as a benchmark for different numerical methods. For similar loading conditions, the target plates containing initial ballistic impact showed a reduced fracture resistance during blast loading compared to the target plates with pre-cut circular holes. Two different numerical approaches were tested and compared, i.e., a purely Lagrangian particle-based approach and a fully coupled simulation approach using an ALE description of the blast domain. The ALE simulations were found to underestimate the structural response, while the particle-based approach overestimated the structural response. Graphical abstract: Highlights: Thin, pre-damaged steel plates were subjected to partially confined blast loading. Pre-damage from either ballistic impacts or pre-cut circular holes. Experimental and numerical investigation of the dynamic response. A purely Lagrangian particle blast method was compared to an ALE method. Ballistic impacts more detrimental for blast resistance than pre-cut holes.